A baseline of terrestrial freshwater and nitrogen fluxes to the Southern California Bight, USA. (September 2021) - Sutula, Martha; Ho, Minna; Sengupta, Ashmita; Kessouri, Fayçal; McLaughlin, Karen; McCune, Kenny; Bianchi, Daniele
Abstract: Time series were compiled of terrestrial nitrogen, phosphorus, carbon, iron, and silica fluxes to the Southern California Bight (SCB), a U.S. West Coast embayment (Sutula et al., 2021). Monitoring data and model output were used to construct a baseline of inputs from direct point source (PS) discharges of wastewater treatment (WWT) effluent (via ocean outfalls) and PS, non-point and natural sources from coastal rivers. The baseline covers 1971—2017 for large WWT plants discharging >50 million gallons per day (MGD) and 1997–2017 for small WWT plants and rivers. PS are the dominant nitrogen source, with contributions of 70% of the total annual freshwater discharge and 95% of nitrogen loads. WWT upgrades have reduced organic nitrogen loads by 73% since 1971. Inorganic nitrogen loads have generally held constant (35–40 Gg y −1 ) for the large WWT plants. This baseline represents a period prior to extensive wastewater and stormwater recycling that is increasing in the region. Highlights: Timeseries of regional terrestrial fluxes over the past several decades is presented. A baseline of human exports is formed considering climate change and water recycling. Wastewater exports are the dominant source of freshwater and nitrogen to the coast. Wastewater treatment plant upgrades have significantly reduced exports since 1971. Orange County Sanitation District is a case study for effects of water recycling.